The Effectiveness of Using Android-Based Mobile Chemistry Learning Media to Increase Students' Interest in Learning Chemistry - Muntari, Muntari; Sofia, Baiq Fara Dwirani; Loka, I Nyoman; Ramlawati, Ramlawati (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Chemistry is a subject that students tend to dislike. Student learning outcomes are still low due to the lack of student interest in learning which is caused by the lack of media used for learning both at home and at school. To overcome this deficiency, interesting learning media is needed as a complement to learning resources that students can use anywhere and anytime, one of which is Android-based mobile learning media. The aim of this research is to determine the effectiveness of using Android-based mobile learning chemistry learning media to increase students' interest in learning chemistry on the topic of buffer solutions. This type of research is Quasi Experimental Design in the form of Nonequivalent Control Group Design. The subjects of this research were students of class XI MIPA 1 and XI MIPA 2 at SMAN 3 Mataram, totaling 58 students. Data collection techniques include interviews and questionnaires. The data analysis used was N-gain score analysis as well as normality, homogeneity and t-tests. The research results showed that the N-gain for the experimental class was 0.618 with medium criteria (effective) while the control class obtained 0.299 with low criteria (not effective). Normality and homogeneity tests showed that the N-gain data was normally and homogeneously distributed. The results of the t-test at the 5% significance level were obtained a significance value showing 0,000 < 0,05. These results indicate that the use of mobile learning media is effective in increasing students' interest in learning chemistry on the topic of buffer solutions.